1989
DOI: 10.1007/bf02441462
|View full text |Cite
|
Sign up to set email alerts
|

Selection of a spectral analysis method for the assessment of velocity distribution based on the spectral distribution of ultrasonic Doppler signals

Abstract: The direct Fourier transform method, autoregressive modelling, the maximum likelihood method and the Wigner-Ville distribution were applied to the Doppler signal obtained from a fully insonated laminar model flow. The appreciation of the spectral method was based on the properties of the ratio variance/(fmean)2 (INT) of the spectrum. The basic criterion was the sensitivity of INT to the analysis parameters, especially the data window. The results of spectral analysis, as well as the properties of INT, were str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…There are also a certain number of original approaches introduced by "Forsberg" and "Strong" et. al, who use decomposition in singular values to evaluate the Doppler frequency [2][3][4][5]. In order to value the parametric signal time-frequency plan, we rewrite the equation under the following matrix form:…”
Section: Time-frequency Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…There are also a certain number of original approaches introduced by "Forsberg" and "Strong" et. al, who use decomposition in singular values to evaluate the Doppler frequency [2][3][4][5]. In order to value the parametric signal time-frequency plan, we rewrite the equation under the following matrix form:…”
Section: Time-frequency Analysismentioning
confidence: 99%
“…Vaitkus et al [10] found that AR modelling yields estimates with variances considerably less than of the periodogram. Kaluzynski [4] reported the better statistical stability of AR spectra in comparison with the periodogram. These studies confirmed the usefulness of AR modeling for Doppler blood flow signal.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, no single TFR is optimal for all signal processing problems, and the choice of the TFR must depend on the specific application. Several authors have demonstrated the limitations of the spectrogram as a tool for analyzing blood velocity patterns [ 3 ] , [4]. Kitney and Talhami [3] showed that a spectrogram-based typical protocol employed in current Duplex scanners is unable to resolve deceleration phase oscillations.…”
Section: E I Introductionmentioning
confidence: 99%